Problems of Orchestra Performance in The Practice of Training Smugglers - Madaminovich, Fozilov Qaxramon (European Journal of Life Safety and Stability (2660-9630), 2021)
Materials of the history of the contrabass art dedicated to contrabass players from different countries - soloists, accompanists of groups of the world’s largest symphony and opera orchestras, teachers - draw attention to a certain stereotype of factual and biographical data. They invariably testify that in the person of the best double bass players there has always been a connection between performance and pedagogy. At the same time, the direct influence of this connection on the process of developing the capabilities of the instrument, its ascent to an equal position among other members of symphonic and chamber ensembles is clearly traced.